ANALISIS KOMPARATIF KINERJA KEUANGAN BERBASIS RASIO PADA PT NIPPON INDOSARI CORPINDO TBK DAN PT TUNAS BARU LAMPUNG TBK - Safirah, Putri Amanda; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the comparative financial performance based on financial ratios of PT Nippon Indosari Corpindo Tbk and PT Tunas Baru Lampung Tbk. The method used is quantitative with a comparative approach. The data consists of annual financial statements analyzed using financial ratios, namely Current Ratio for liquidity, Debt to Equity Ratio for solvency, and Return on Assets (ROA) for profitability. The results show differences in financial performance between the two companies based on each ratio. Companies with better ratios demonstrate stronger ability in meeting obligations, managing capital structure, and generating profits through assets. This study is expected to provide evaluation material for companies and a reference for future research.